Unsaturated fatty acids suppress interleukin-2 production and transferrin receptor expression by concanavalin A-stimulated rat Iymphocytes - Philip C. Calder; Eric A. Newsholme (Mediators of Inflammation)
The proliferation of T-lymphocytes is dependent upon their ability to synthesize and secrete the cytokine, interleukin-2, and to express cell surface receptors for interleukin-2 and transferrin. We have previously reported that certain fatty acids inhibit mitogen-stimulated T-lymphocyte proliferation. We now report that unsaturated fatty acids decrease the concentration of interleukin-2 in the culture medium of such cells by up to 45%. This suggests that unsaturated fatty acids inhibit lymphocyte proliferation by suppressing interleukin-2 production. However, lymphocyte proliferation was only partially restored by addition of exogenous interleukin-2 to cell culture medium in the presence of unsaturated fatty acids, indicating that these fatty acids also affect other processes involved in the control of proliferation. Saturated fatty acids, which also inhibit lymphocyte proliferation, did not affect the interleukin-2 concentration in the culture medium suggesting a different mechanism for their action. Neither saturated nor unsaturated fatty acids affected the expression of the interleukin-2 receptor by mitogenstimulated lymphocytes. In contrast, unsaturated fatty acids decreased expression of the transferrin receptor by up to 50%. These observations suggest that the mechanism by which unsaturated fatty acids inhibit lymphocyte proliferation involves suppression of interleukin-2 production and of transferrin receptor expression. The mechanism for the inhibitory action of saturated fatty acids is not clear.